La vida global (En la Eco-bio-tecno-noos-fera) - Espinosa Rubio, Luciano (Logos. Anales del Seminario de Metafísica, 2007)
Nowadays is necessary to understand Life in a global way and that means to consider several dimensions of the topic at the same time: the ecological and the biological ones, but also the technical and symbolic ones, because we are just living –as it is well known– in a great “net-world”. The interdependence is the key, above all when Nature and Culture interact and integrate the new ecosystem of the planet Earth as never they did before, and all that includes many challenges and risks too.